2015
DOI: 10.3390/nano5041955
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Photocatalytic Activities of the Colloidal ZnS:Mn Nanocrystals Prepared at Various pH Conditions

Abstract: Water-dispersible ZnS:Mn nanocrystals (NC) were synthesized by capping the surface with mercaptoacetic acid (MAA) molecules at three different pH conditions. The obtained ZnS:Mn-MAA NC products were physically and optically characterized by corresponding spectroscopic methods. The UV-Visible absorption spectra and PL emission spectra showed broad peaks at 310 and 590 nm, respectively. The average particle sizes measured from the HR-TEM images were 5 nm, which were also supported by the Debye-Scherrer calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…However, the degree of aggregation for the ZnS:Mn-Asp NCs was relatively low in water compared to other aminoacids capped ZnS:Mn NCs, which was probably due to the electrostatic repulsion between the negatively-charged NC surfaces. A similar phenomenon has been seen with ZnS:Mn-MAA NCs prepared at pH 7, with the formation of much larger agglomerates in water than at pH 2, in which the repulsion between the NCs was significantly reduced [ 40 ].…”
Section: Resultssupporting
confidence: 69%
“…However, the degree of aggregation for the ZnS:Mn-Asp NCs was relatively low in water compared to other aminoacids capped ZnS:Mn NCs, which was probably due to the electrostatic repulsion between the negatively-charged NC surfaces. A similar phenomenon has been seen with ZnS:Mn-MAA NCs prepared at pH 7, with the formation of much larger agglomerates in water than at pH 2, in which the repulsion between the NCs was significantly reduced [ 40 ].…”
Section: Resultssupporting
confidence: 69%
“…Figure A represents a series of time-resolved PL decay traces measured at 590 nm in chloroform solutions of doped Mn:ZnSe nanocrystals passivated by SA ligands and with varying concentrations of DHV 2+ . This system allowed us to investigate whether the doped Mn:ZnSe nanocrystals are able to undergo PET processes in nonaqueous solutions because such systems are relevant to photocatalytic C–C bond formation and degradation of pollutants, for example. ,, The measurements utilized 355 nm excitation at 26 μJ/cm 2 intensity. The time-resolved PL trace of the sample with 0 nM DHV 2+ has the same long excited state lifetime as the data presented in Figure B.…”
Section: Resultsmentioning
confidence: 99%
“…The doping with transition metal Mn 2+ can introduce new states within the band gap of host, and the doping Mn 2+ can act as shallow traps to prolong the lifetime of photo-generated carriers. Most of the as-reported Mn-doped ZnS possess cubic zinc blende structures and were used as photocatalysts for photodecomposition of different organic dyes under UV-Vis light illumination [19][20][21][22]. R. Nasser's group studied the effect of Mn doping on photoluminescence and photocatalytic behaviors of Zn1−xMnxS, their results showed that Mn 2+ luminescent ions promoted the charge separation and played an important role in its excellent photocatalytic activity [19].…”
Section: Introductionmentioning
confidence: 99%